THERMODYNAMICS OF THE ANION ORDERING TRANSITIONS IN (TMTSF)2REO4 AND (TMTSF)2BF4 - CHUNG, M; FIGUEROA, E; KUO, YK; WANG, YQ; BRILL, JW; BURGIN, T; MONTGOMERY, LK (AMERICAN PHYSICAL SOC, 1993)
We have studied the anion ordering transitions in the Bechgaard salts, (TMTSF)2ReO4 and (TMTSF)2BF4 using ac calorimetry, differential scanning calorimetry, and the vibrating-reed technique. An analysis of the sensitivity of ac calorimetry to (distributed) molar latent heat l(T) is presented. For the ReO4 salt, the transition is weakly first order, exhibiting no sluggishness or hysteresis. The effective specific heat measured using ac calorimetry, i.e., c(p) + dl/dT, exhibits a lambda-like anomaly, but the entropy of the transition is sample dependent and generally less than the expected value, R ln(2). In comparison, the transition is sluggish for the tetrafluoroborate salt, so that only a lower limit on the entropy could be determined. The thermal anomalies are compared to the anomalies observed using the vibrating-reed technique; the latter are affected by changes in the lattice constants as well as the Young's moduli at the transitions.
Keywords: DIFFERENTIAL SCANNING CALORIMETRY; METAL-INSULATOR-TRANSITION; LOW-TEMPERATURE PHASE; ELASTIC ANOMALIES; HEAT; PERRHENATE; DEPENDENCE; VELOCITY; SALTS; TMTSF